PENERAPAN MODEL CONTEXTUAL TEACHING LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 55 KESUMBO AMPAI KECAMATAN MANDAU KABUPATEN BENGKALIS - Melati, Melati; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : The problem in this research was natural studies students achievement in five graderes (VA) SDN 55 Kesumbo Ampai stil low with average value 55,36(with KKM 65).The purpose of this research was to improve the students achievement of the five graderes(VA)SDN 55 Kesumbo Ampai ,with the implementation Contextual teaching and learning.This research was an classroom action research with two cycles in second semester 2014/2015.Before implementation Contextual teaching and learning average62,5%, after implementation contextual teaching and learning ,UH I was 66,61 that improve 35 % from before exam with average 55,36 .UH II was 75,54 that improve 52,86% .Teacher’s activities with the implemettation of contextual teaching and learning at firs meeting of firs 62,5% (good category),and second meeting was 68,75%(good category) at second cycle,student activities at first.Second meeting of second cycle was 93,75%.Implementation contextual teaching and learning improve natural studies students achievement of five graderes (VA)SDN 55 Kesumbo Ampai Kecamatan Mandau kabupaten Bengkalis.Key word : contextual Teaching and learning,natural studies student‟s Achievement2